Apakah Stress dengan Aktivitas Fisik berkorelasi dengan Tingkat Nyeri Dismenore Primer? - Apriwiliyanti, Anggy Nur; Wahyuni, Wahyuni (Griya Widya: Journal of Sexual and Reproductive Health, 2023)
Background: Dysmenorrhea occurs when menstrual cramps are caused by substances (prostaglandins) that cause the uterine muscles to contract. Stress is an individual's reaction to a threatening situation or event and can affect their ability to cope Objective: of this study was to determine the correlation between stress levels on physical activity and primary dysmenorrhea pain levels experienced by female adolescents. Method: used is analytic observation with a cross sectional approach and is a quantitative research type. The independent variable is stress and the dependent variable is dysmenorrhea pain and physical activity. Using the PSS-10, IPAQ, and NRS Questionnaires Result: the study showed moderate stress levels in 65 of 86 female students (75.6%). The most physical activity was in the moderate category, namely 69 out of 86 female students (80.2%). The most dysmenorrhea was in the moderate category, namely 28 out of 86 female students (32.6%). There is no correlation between stress levels and physical activity in female students with a p-value of 0.417 > 0.05. There is no correlation between stress levels and primary dysmenorrhea pain levels in female students with a p-value of 0.055> 0.05. Conclusion: There is no correlation between stress and physical activity and the level of dysmenorrhea pain in female students at SMP N 2 Margoyoso.